Soil moisture dynamics in water- and energy-limited ecosystems. Application to slope stability (2019)
I investigate the daily dynamics of the soil-water-climate system in water- and energy-limited environments. I analyze the stochastic component of radiation at the Earth's surface in the photosynthetically active spectral band in 28 sites located around the world and propose a clear-sky based methodology to model it. In order to study the e_ect of stochastic radiation on soil moisture and evapotranspiration, we use the proposed radiation model and the ecohydrological model of Rodr__guez-Iturbe et al. I introduce a semi-analytical equation to analyze the dynamics of evapotranspiration as a function of stochastic rainfall and radiation. With climatic and physiological measurements from the FLUXNET dataset, and taking into account the coupling of water and CO2 uxes through the leaf plant, I parameterize the link of transpiration and available energy, which is used to extend the ecohydrological model to energy-limited ecosystems. Finally, I carry out an application to landslides triggered by rainfall, relating the factor of safety of a slope to soil moisture, and examine the widely used threshold rainfall approach to estimate the landslides occurrence.